DEVELOPMENT OF COMICS AS AN EDUCATIONAL MEDIUM FOR BULLYING PREVENTION EFFORTS FOR JUNIOR HIGH SCHOOL STUDENTS - Nur, Een Afliani; Febriati, Farida; Hakim, Abdul; H, Nurhikmah (JURNAL NALAR PENDIDIKAN, 2025)
Comic development serves as a medium to deliver information more clearly and understandably. This study aimed to identify needs, design, validate, and assess the practicality and effectiveness of the product. The method combined elements from the Four-D, Dick and Carey, and ADDIE models. Product practicality, evaluated through questionnaires by students and counseling teachers, was rated very high. Effectiveness testing using pretest and posttest with the Wilcoxon Signed Rank Test showed improved student understanding of verbal and social bullying. Thus, the educational comic proved effective in preventing bullying at school.